2016
DOI: 10.1080/10790268.2016.1213554
|View full text |Cite
|
Sign up to set email alerts
|

Impact of bladder, bowel and sexual dysfunction on health status of people with thoracolumbar spinal cord injuries living in the community

Abstract: Results highlight the high prevalence of self-reported bowel/bladder incontinence and sexual dysfunction in the traumatic thoracolumbar SCI population and support the need for standardized assessments. Several demographic, injury-related and SHCs impacted health status and should be considered for the management of individuals living in the community.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 56 publications
2
21
0
1
Order By: Relevance
“…As in previous studies, we found some of the SHCs (spasms and pain) co-occurred (Brinkhof et al 2016 ; Park et al 2017 ). Brinkhof et al’s ( 2016 ) survey on health conditions in people with SCI found clustering of sexual dysfunction, spasticity, bowel dysfunction, pain, bladder dysfunction and urinary tract infections (Brinkhof et al 2016 ).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As in previous studies, we found some of the SHCs (spasms and pain) co-occurred (Brinkhof et al 2016 ; Park et al 2017 ). Brinkhof et al’s ( 2016 ) survey on health conditions in people with SCI found clustering of sexual dysfunction, spasticity, bowel dysfunction, pain, bladder dysfunction and urinary tract infections (Brinkhof et al 2016 ).…”
Section: Discussionsupporting
confidence: 88%
“…Equally, depression and anxiety have been reported to increase the risk of SHCs such as urinary tract infections, pain and spasms (January et al 2014 ). Park et al ( 2017 ) found 29% of participants with SCI reported experiencing a combination of sexual dysfunction, bowel and bladder incontinence with a high association between these SHCs. The possible reason for the SHCs co-occurrence could be because of the same parasympathetic innervation to the bowel, bladder and reproductive organs.…”
Section: Discussionmentioning
confidence: 99%
“…2,[13][14][15] In 1998, Post et al 10 used path analysis to examine the complex relations among aspects of SCI, health conditions, and personal factors (eg, age) with health-related quality of life (HRQoL) and life satisfaction, demonstrating that severity of SCI, number of health conditions, and personal factors (eg, older age) can all negatively affect HRQoL factors (eg, physical and mental health, life satisfaction). In addition to the association with participation, HRQoL, and life satisfaction, other previous studies have demonstrated that a count of health conditions is more predictive of both health status 16 and health care utilization 17 than other demographic or injury factors. 10,18,19 The management of multiple health conditions (or multimorbidity) may be difficult because treatment of coexisting health conditions may conflict and exacerbate others; physicians have expressed that they are often overwhelmed when deciding on management of multiple health conditions.…”
mentioning
confidence: 96%
“…Sexual dysfunction can manifest in a number of different ways in males and females, depending upon the level and completeness of the injury [ 117 ]. In addition to the physical impact, sexual dysfunction in particular may impact psychological wellbeing and overall quality of life [ 119 , 120 ]. Gastrointestinal disturbances in SCI are common (>60%) and wide-ranging, including delayed gastric emptying, abnormal colonic myoenteric activity and sphincter/defecation dysfunction [ 117 , 121 , 122 ].…”
Section: Neurostimulation For Autonomic Recovery Following Scimentioning
confidence: 99%